Kajian Yuridis Terhadap Tindakan Pencemaran Nama Baik - Aftar Akbar; Khaerul Mannan; Iswandy Rani Saputra (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
This study aims to find out about the application of criminal law in Decision No.219/Pid.Sus/2019/Pn.Pre and also to find out about the legal considerations of judges in imposing Decision No.219/Pid.Sus/2019/Pn.Pre. The type of research to be carried out is the normative approach method. The normative approach or commonly referred to as doctrinal research is an approach that is carried out by means of regulations reviewing literary materials such as legislation, theories, and legal principles related to the problem being tested. The application of the criminal law for defamation based on the Decision of the Parepare District Court No.219/Pid.Sus/2019/PN.Pre which states that the prosecution of the public prosecutor is unacceptable and the Defendant is immediately released from Detention is correct and appropriate based on applicable law. Furthermore, the legal considerations of the case judge No.219/Pid.Sus/2019/PN.Pre stated that the phrase in Article 319 of the Criminal Code, namely